Determining Factors that Affect Tax Professional’s Ethics Intention - Yenni Mangoting; Maria Anastasia Fidelis Foek; Stella R. Gomaz (Universitas Negeri Semarang, 2024)
Purpose: This study aims to forecast the inclinations of tax professionals to engage in ethical conduct within their work setting, by examining the impact of their immediate social circle, personal attitudes, and organizational support. Method: The study utilizes a sample of individuals, both as tax consultant business owners and tax professionals working in a company. Data collection was conducted by distributing questionnaires through Google Forms. A total of 90 questionnaires were analyzed using Partial Least Squares. Findings: The findings of this study identify that perceived organizational support and subjective norm has a role in influencing the ethical intentions of tax professionals. Furthermore, it is proven that the attitude of tax professionals can mediate the impact of perceived organizational support on ethical intentions. In fact, the role of attitude, influenced by subjective norm, has a greater influence on enhancing the ethical intentions of tax professionals compared to the absence of subjective norm without the role of attitude aspect. The variable in question exhibits an inverse relationship with perceived organizational support, wherein the latter exerts a more significant impact independent of attitude mediation. Novelty: This research is beneficial for regulators and professional associations as regulators to systematically enhance integrated organizational support within the work environment to influence the ethical intention of tax professionals.